Pelatihan Pengemasan Sayur Hidroponik dan Pemasaran Berbasis Multimedia Sebagai Upaya Peningkatan Keterampilan Siswa SLBN Jember - Rindha Rentina Darah Pertami; Trismayanti Dwi Puspitasari; Jumiatun Jumiatun; Arvita Agus Kurniasari; Azizah Afni Maulidiyah (Journal of Community Development, 2025)
Jember State Special School (SLB) through the Pancasila Student Profile Strengthening Project (P5) vocational through the theme "Let's garden". The implementation of the project has several obstacles, namely the limited number of teachers in managing the number of students if they have to do direct practical activities. So that a visual, communicative, and interesting learning method is needed so that students can easily understand it. The purpose of this activity is to improve the skills of SLB N Jember students. The implementation time is from May to August 2024. The methods used include observation, training in practice, monitoring, and evaluation. They are learning with visual or props techniques Based on the results of the activities that have been carried out. That there are 81% of students understand hydroponic vegetable packaging, and 60% of students who can understand the concept of packaging design, and marketing carried out through WhatsApp business so that they can improve their Agro-Entrepreneurship skills. This activity hopes to foster an entrepreneurial spirit in students as a provision after school. The training uses a learning system with visual or props techniques assisted by teachers at school. This activity continues to be accompanied by monitoring and evaluation so that it can be sustainable.